PWE-438 Cholecystectomy audit: waiting time, readmissions and complications. (22nd June 2015) - Gill, MS; Doherty, C; Veitch, J; Brett, M
Abstract : Introduction: 15% of the UK adult population have gallstones. In those with symptomatic gallstone disease, laparoscopic cholecystectomy is the gold standard management. 1 There continues to be debate over whether patients should undergo definitive management at presentation or it should be delayed until inflammation has subsided. Guidelines suggest patients with acute cholecystitis should be offered cholecystectomy within 1 week 1, while those with gallstone pancreatitis should receive therapeutic ERCP within 72 h followed by cholecystectomy within the same hospital admission, or within 2 weeks. 2 Method: A retrospective audit of all cholecystectomies at the trust over a 1-year period was performed. Data extracted from electronic medical records (Medicorr) was collated using Microsoft Excel. Patient demographics, diagnosis at initial presentation, time to surgery, and rate and cause of readmission of those awaiting elective surgery were recorded. Chi-Squared analysis was performed to assess for a significant difference between elective and emergency lap-open conversion and complication rates. Results: 477 patients were included. The median age was 51 years and 80% were female. The most common indications for cholecystectomy were biliary colic (69%) and cholecystitis (23%). The median wait for surgery was 81 days. The median wait for patients with acute cholecystits and gallstone pancreatitis was 69 and 62 days respectively. 8% of patients were readmitted while waiting. Those discharged after presenting with complicated gallstone disease (common bile duct stones or gallstone pancreatitis) were most likely to require readmission (27% and 24% respectively). Acute cholecystitis was the most common diagnosis on readmission (56%). 5 patients were readmitted with gallstone pancreatitis. The laparoscopic to open conversion rate was not significantly greater in emergency operations compared to elective (p > 0.05). The complication rate of emergency operations, however, was significantly greater compared to elective (p < 0.05). Conclusion: Guidelines for performing urgent cholecystectomy for patients with gallstone pancreatitis and acute cholecystitis were not met for the majority of patients. A significant proportion were admitted to hospital while awaiting cholecystectomy, some with serious complications of gallstones. It appears that patients with complicated gallstones disease are more likely to be readmitted. We are continuing to collect data to attempt to identify high-risk patients. There may be a role for "elective-emergency" lists for such patients, to prevent complications developing. We plan to re-audit in one year to identify improvement. Disclosure of interest: None Declared. References: NICE Clinical Guidance 188 – Gallstone Disease British Society of Gastroenterology: UK guidelines for the management of acute pancreatitis. Gut 2005;54;1–9